ڈاکٹر فاروق احمدخان کی تفسیری خدمات اور آپ کے تفردات کا تجزیاتی مطالعہ : An Analytical Study of Dr. Farooq Ahmed's Tafsir Services and His Distinctions - Begum, Liaqat (Al-Amīr Research Journal for Islamic Studies, 2023)
For the guidance of humanity, God revealed the Holy Quran. It is the only book which is recited the most. Those who read and teach this book have been called the best people. From the blessed life of the Holy Prophet (ﷺ) till today, scholars have tried their best to make common sense for the less educated people. And Muhadithin have to bind chapters of "Kitab al-Tafseer and Chapters of Commentary" in their own books. Companions and many commentators interpreted. Some of the interpretations were translated into different languages ​​so that common people can benefit from it. Scholars of the Indian sub-continent also interpreted the Holy Quran for the understanding of common people. A link in the same series is Dr. Muhammad Faruk Khan's "Asan Tarin Tarjuma Wa Tafsir" which is written in simple Urdu language. Dr. Sahib's distinctions on special topics make the reader ponder. In this article, Dr. Farooq Ahmad Khan's services regarding Tafsir and his distinctions about (Alphabets, prohibited trees, forgetfulness of Adam, etc.) will be examined. Along with the opinions of different commentators will also be present. Keywords: Qura’n, Dr. Farooq Ahmad, Asan Tarin Tarjuma wa Tafsir, distinctions, Commentators.